Buste Rodríguez,Jeniffer Lizeth(2023)Activadores del sistema radicular en el cultivo de banano (Musa paradisiaca) variedad Gran Williams.Quevedo.UTEQ.84p. - Buste Rodríguez , Jeniffer Lizeth (2023)
Banana is one of the main crops grown worldwide, providing economic income and sources of work, contributing to the food security of millions of people; activators have shown positive effects on crop development, helping the plant to have a greater assimilation of nutrients and a better root system. The main objective of this research is to evaluate the behavior of root system activators in the Gran Williams variety banana crop, using the completely randomized block design (DBCA), to evaluate the effect of activators on the root system with four treatments, three replications and five experimental units. The results obtained in the physiological development in treatment 2 (1,875g of urphos +150g of boric acid) obtained a greater result based on the treatments evaluated, presenting a diameter of 39.9 cm at the beginning and ending at 90 days with 62.9 cm, the responses to the various doses of applications of activators via drench were given in treatment 3 (3,750g of urphos + 150g of acid) obtaining a weight of 81. 07g, the most effective activators of the root system were treatment 2 with a final weight of 15.60g, as a result in variable plant height, yielded a higher average in the treatment T2 of 2.21 (30dda), 2.41(60dda), and 2.57 (90ddia). These results exposed in this experiment cause effective effects for a better production.